2020
DOI: 10.1016/j.jqsrt.2020.107261
|View full text |Cite
|
Sign up to set email alerts
|

Experimental assessment of the sudden-reversal of the oxygen dilution effect on soot production in coflow ethylene flames II: soot radiation and flame transition analysis

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The trend reversal was attributed to a change in the overall flame structure, specifically the inner premixed reaction zone and the outer diffusion flame. A follow-up study [49] to [45] suggested that the dilution effect of oxygen was a monotonic decrease in soot formation up to a mole fraction of about 40%, but the chemical effect of oxygen displayed a reversal at an oxygen mole fraction of 32%. No explanation was given regarding the kinetic mechanism that causes the reversal.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The trend reversal was attributed to a change in the overall flame structure, specifically the inner premixed reaction zone and the outer diffusion flame. A follow-up study [49] to [45] suggested that the dilution effect of oxygen was a monotonic decrease in soot formation up to a mole fraction of about 40%, but the chemical effect of oxygen displayed a reversal at an oxygen mole fraction of 32%. No explanation was given regarding the kinetic mechanism that causes the reversal.…”
Section: Resultsmentioning
confidence: 99%
“…One school of thought suggests that the reduction of soot is solely dependent on the quantity of oxygen [11], [47]. Experimentation has also shown that in small amounts, diatomic oxygen addition can increase soot production [48], [49]. Additionally, synergistic effects have been seen when mixing oxygenated fuels with hydrocarbon fuels increasing soot production rates [20][21][22].…”
Section: Molecular Oxygen Additionmentioning
confidence: 99%